Ambulance provision for children: a UK national survey. (29th September 2015) - Houston, R; Pearson, G
Abstract : Aims: The purpose of this national survey of UK ambulance services was to provide an up-to-date assessment of service provision for children in the prehospital setting. The survey also sought to identify challenges faced by services in providing optimal services to this group. The findings help inform future service provision and set the context for further audit, research and confidential enquiry. Method: A questionnaire was sent to Clinical Directors of the 16 UK NHS ambulance services in April 2009. Non-responders were followed up three times after the initial deadline. Results: Questionnaires were returned by 13 (81%) respondents. Paramedics and most emergency medical technicians receive a limited amount of paediatric training. Only a minority undertake certified courses (eg, PHPLS, PEPP). An increasing amount of equipment suitable for children is becoming available and paramedics are permitted to use more skills than in the past. However, services for children vary depending on location. Some children's needs are not met due to insufficient equipment or inadequate skills. For example, paediatric airway adjuncts (short of intubation) were often lacking and only 62% reported having pulse oximetry suitable for use in children. A third of services (4/13) considered it "possible or highly likely" that someone with no specific training could be the first to respond to a child in an emergency, and over half (7/13) indicated that the likelihood that the first response to a child could be someone with no current recognised certified qualification specific to paediatrics was "high". There are also large areas of the country where no additional medical support is available at any time of day. Conclusions: The prehospital phase of a child's care pathway is part of a continuum and cannot be viewed in isolation. Despite improvements, paediatric care by frontline personnel is limited by resources and skill availability and, when assessed by comparison by national guidelines (eg, JRCALC), accepted standards are often lacking. Audit, research and training initiatives should be carried out collaboratively between ambulance services and acute trusts to guide training, local service requirements and resource allocation. This will reduce variation and maintain the safety of patients and quality of care.